Evaluation system for e-learning - Zekanović-Korona, Ljiljana; Krce Miočić, Božena; Mateljan, Vladimir (2012)
Education is essential part of each society and by studying e-learning systems, without which any contemporary society is unimaginable, We wanted to create an evaluative model of e-learning systems. The purpose of this model is to direct and help the authors of educative contents to create the most qualitative teaching materials. The advantage of e-learning is the possibility of learning from one’s own home comfort and when it mostly suits an individual. E-learning puts emphasis on adjusting lecturing contents to individuals and their educative motivations. With empirical research used in this work, I have proved that there are statistically significant connections between all elements of e-learning system ; education materials structure, teaching methods, accessibility, interest and availability of education materials, motivation and users' activity, development of creativity, research approach, back up information, illustrated examples, education materials design, communication within e-learning system, users’ role, support to users and implementation of knowledge evaluation. The most important proved connections are between the methods of education and the structure of educational contents, research approach and the development of creativity in system users, their role, communication within e-learning system and motivation of its users.
Projekt MZOS
ENG